Analisis Komparatif Usahatani Pisang Cavendish Menggunakan Sistem Irigasi Tetes Dan Konvesional (Kasus di Desa Mekarjaya Kecamatan Kabupaten Indramayu) - Arsy Al Dzismi; Dwi Purnomo; Farida Mardhatilla (Paradigma Agribisnis, 2024)
This research aims to determine the comparison of income and Break Even Point in Cavendish Banana farming which uses Drip and Conventional Irrigation Systems. The sampling technique uses the census method (total sample). Samples were taken from all members of the population from 10 Cavendish Banana farmers with a Drip Irrigation system and 10 farmers with a Conventional System. The results of research on Drip Irrigation systems with an average cost per hectare of Rp. 35.892.000,00 and conventional systems 35,092,000. The average income per hectare of farmers from the Drip Irrigation system is IDR. 761,600,000 and the Conventional system is Rp. 513,000,000 The average income per hectare of Cavendish banana farmers with a drip irrigation system is IDR. 740,185,000 and conventional farming systems, namely Rp. 478,500,000. The BEP value for Cavendish banana production from the drip irrigation system is 2,600 kg, and the conventional system is 2,900 kg. The BEP value for the price of Cavendish banana farming for the drip irrigation system is IDR 6,700/kg, and the conventional system is IDR 8,500/kg. The safe limit for reducing the price of Cavendish bananas for drip irrigation systems is 52.13%, and for conventional systems the price reduction is 29,17%. From the results, there are differences in costs, income, and BEP in Cavendish banana farming with a drip irrigation system and Cavendish banana farming with a conventional farming system. Keywords: Comparative, Cavendish Banana, drip irrigation, conventional irrigation